ANALYSIS OF FACTORS THAT EFFECT THE PERFOMANCE OF INSEMINATORS IN YHE IMPLEMENTATION OF THE UPSUSSIWAB PROGRAM IN BADUNG REGENCY - I G. M., Dwipayana; Suranjaya, I G.; Sarini, N. P. (Jurnal Peternakan Tropika; Vol 9 No 1 (2021): Vol. 9 No. 1 Tahun 2021; January - april, 2021)
Inseminators are one of the factors that play an important role in artificial insemination confidence in the UPSUS SIWAB program launched by the government to increase the cattle population in Indonesia. This study aims to determine the factors that influence inseminator performance and to believe artificial insemination (IB) in an effort to support the UPSUS SIWAB program in Badung Regency. This research was conducted by survey method and the sample was taken by purposive sampling..The variables sought are constituent factors including: age, length of education trip, number of families, compilers working time, length of time as a spreader, operational distance and location and compiler performance includes: number of IB per year, proportion of IB once, proportion of Conception Rate and proportion Calving Rate. Data analysis was carried out descriptively with multiple regression methods and explored using a stepwise method to identify the most influential factors. The results showed that the performance of the inseminator was jointly influenced significantly (P <0.005) by age (X 1 ), length of study (X 2 ), total family members (X 3 ), work time of inseminator (X 4 ), length of time as an inseminator (X 5 ), working operational distance (X 6 ), and location (D i ). Through stepwise analysis, it is found that the number of livestock that can be AI per year (Y 1 ) is significantly influenced by D 1 with the equation (Y 1 ) = 1275,178 - 422,978 D 1 with R 2 = 0.420. For the success of one time AI (Y 2 ) is influenced by X 1 and X 2 with the equation Y 2 = 71.770 + 1.038 X 1 + 1.970 X 2 with R 2 = 0.701. Meanwhile, for the conception rate (Y 3 ) and the calving rate (Y 4 ) are influenced by X 1 and X 2 with the equation Y 3 = 0.621 + 0.012 X 1 + 0.023 X 2 with R 2 = 0.477, and Y 4 = 0.573 + 0.011 X 1 + 0.017 X 2 with R 2 = 0.371. For the factors that identified, it turns out that the variables of age (X 1 ) and length of study (X 2 ) have the most role in the performance of the inseminator in supporting the success of AI in the implementation of the UPSUS SIWAB program in Badung Regency. Key words : inseminator, artificial insemination, upsus siwab